The Effectiveness of the Think Talk Write (TTW) Learning Technique Aided by Word Cards Media in Improving Sentence Writing Ability - Yuli Nurhayati; Lina Siti Nurwahidah; Jamilah Jamilah (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This research aims to examine the effectiveness of the Think Talk Write (TTW) technique supported by word cards in enhancing sentence writing skills. The research method is quasi-experimental, utilizing a nonequivalent group's pretest-posttest design. Data collection techniques encompassed sentence writing tests and angle distribution. The research sample comprised Class IX C as the experimental group and Class IX A as the control group. Data processing techniques included the Shapiro-Wilk test to assess data normality, paired sample T-tests, and the NGain-Score test. The paired sample T-tests for the experimental group yielded a Sig. (2-tailed) value of 0.00 < 0.005, indicating a significant distinction between the pretest and posttest scores. Similarly, the paired sample T-test outcomes for the control group demonstrated a Sig. (2-tailed) value of 0.00 < 0.005. Moreover, based on the NGain-Score calculation, the average gain score for the experimental group was 71.25. In contrast, for the control group, it stood at 50.28, implying that the Think Talk Write (TTW) model, supplemented by word cards, effectively improves sentence writing skills.